THE MEANING OF OPENING TEASER OF THE TALK-SHOW DUA SISI AS PROGRAM IDENTITY - Oktora, Dina Dwika (Capture : Jurnal Seni Media Rekam, 2020)
A television program is usually equipped with an opening teaser as the identity of the program. The opening teaser on TVONE's show, entitled "Dua Sisi" (Two Sides) looks simple but interesting to study. This research focuses on the meaning of the sign in the opening teaser of "Dua Sisi". This study used a qualitative descriptive approach. Data collection used purposive sampling technique, and data analysis used Rolland Barthes' Semiotics. The results showed that the meaning of the signs contained in this event had denotative and connotative meanings in accordance with the function of the opening teaser as the identity of the program.